The development of music - Howell, Annice (My University, 1908)
Introduction: Liszt defines music as “the universal language of mankind by which human feelings are made equally intelligible to all; whilst on the other hand it offers to the different nations the most varied dialects, according to the mode of expression suitable to the character of each nation.”
Citation: Howell, Annice. The development of music. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Music; Music History; Handwritten; Graduating theses; Senior theses; Theses